Polarization of Islamic Boarding Schools in Response to Government Policies in The Implementation of Education During The Covid-19 Pandemic from A Crisis Management Perspective - Ahmad zain Sarnoto (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article examines the perspective of crisis management regarding the response of Islamic boarding schools to government policies in handling the transmission of the COVID-19 pandemic, where there is polarization among Islamic boarding schools in carrying out their education patterns, some follow government recommendations in carrying out health protocols and some refuse. This type of research is library research with qualitative methods. Data were collected from library sources with a sociological approach. The theory used is crisis management. The findings of this study are as follows: first, the occurrence of pros and cons of pesantren in responding to change. Second, the Polarization of Islamic Boarding Schools in carrying out education management patterns in the midst of the Covid-19 pandemic. This research contributes to efforts to improve education management in Indonesia in general.